A case of dystonic spasms in an adolescent: A neurologist’s enigma! - Kaur, Deepinder Maini; Tomar, Nishant; Rehani, Varun; Anand, Rajiv (Indian Journal of Case Reports, 2024)
A 15-year-old boy presented with episodic abnormal movements of the right upper limb, neck, and jaw for 10 days associated with pain and spasms, following a penetrating injury to his right hand 2 months ago. He was successfully managed for tetanus with antitoxin, antibiotics, wound debridement, and supportive care. He was found to have protective tetanus antibody levels (1.1 IU/mL). To encounter tetanus in a vaccinated individual with an atypical focal presentation is a cause for concern and requires awareness to avoid delay in diagnosis and management.